Percutaneous Tibial Length Measurement for Estimation and Correlation of Stature in Nepalese Males - Poudel, Abhishek; Satyal, Biswas (Journal of Nepalgunj Medical College, 2017)
Introduction: Estimation of stature is an important step in identification of an individual, which often is required in medio-legal practice. It provides a valuable indicator for unknown individual in a population. Through the remains of human skeletal or body parts stature of an individual can be estimated. Methods and Materials: Percutaneous tibial length (PCTL) is measured in present study to estimate the stature by formulating simple regression equation. The PCTL was measured by the surface anatomical landmarks that is between most prominent part of medial condyle of tibia and tip of medial malleolus. Result: Positive correlation was found between the length of tibia and estimated height. A linear regression formula was derived for estimation of height from the length of right and left tibia. Conclusion: Estimated height and observed height were closely related within the range of error. Differences in length of right and left tibia showed statistically non-significant.